Characteristics of Wall Shear Stress and Pressure of Intracranial Atherosclerosis Analyzed by a Computational Fluid Dynamics Model: A Pilot Study - Chen, Zimo; Qin, Haiqiang; Liu, Jia; Wu, Bokai; Cheng, Zaiheng; Jiang, Yong; Liu, Liping; Jing, Lina; Leng, Xinyi; Jing, Jing; Wang, Yilong; Wang, Yongjun (Frontiers in Neurology, 2020)
Background: Although wall shear stress (WSS) and pressure play important roles in plaque vulnerability, characteristics of the two indices in intracranial atherosclerosis (ICAS) have not been fully investigated yet. This study aimed to elucidate this issue by means of establishing a noninvasive computational fluid dynamics (CFD) method with time-of-flight magnetic resonance angiography (TOF-MRA) of whole cerebral artery. Material and Methods: Subjects with symptomatic ICAS in middle cerebral artery domain were enrolled, excluding those with concomitant internal carotid artery stenosis. Based on patient-specific TOF-MRA images for 3-dimensional (3D) meshes, and arterial blood pressure with patient-specific carotid artery ultrasonography for inlet boundary conditions, patients’ 3D hemodynamics were modeled by a finite element method governed by Navier-Stokes equations. Results: Among the fifty-five atherosclerotic lesions analyzed by this TOF-MRA based CFD model, the maximum WSS (WSSmax) was most frequently detected at the apex points and the upper half of the upstream sections of the lesions, whereas the maximum pressure was most often located at the lower half of the upstream sections. As the percent stenosis increases, the relative value of WSSmax and pressure drop increased with significantly increasing steep beyond 50% stenosis. Moreover, WSSmax was found to linearly correlate with pressure drop in ICAS. Conclusions: This study on ICAS revealed certain trends of longitudinal distribution of WSS and pressure and the influences of percent stenosis on cerebral hemodynamics, as well as the correlations between WSS and pressure drop. It represents a step forward in applying computational flow simulation techniques in studying ICAS and stroke, in a patient-specific manner.